A One‐Pot Access to Benzo[b][1, 4]selenazines from 2‐Aminoaryl Diselenides. Issue 18 (15th June 2016) - Menichetti, Stefano; Capperucci, Antonella; Tanini, Damiano; Braga, Antonio L.; Botteselle, Giancarlo V.; Viglianisi, Caterina
Abstract : Different 2‐sulfonylaminoaryl diselenides substituted with electron‐withdrawing or ‐donating groups are transformed in one pot into benzo[ b ][1, 4]selenazines. The reaction uses a substoichiometric amount of Cu(OTf)2, and the mechanism involves a base‐mediated 1, 4‐elimination at selenium with the generation of an o ‐iminoselenoquinone and a 2‐sulfonylaminoselenolate anion. The former is a dienic species that can react with electron‐rich dienophiles to give the target cycloadducts. The latter is oxidised by air back to the starting diselenide, allowing its complete consumption. A preliminary investigation of the GPx‐like activity of a selected selenazine is also described. Abstract : 2‐Sulfonylaminoaryl diselenides are transformed in one pot into benzo[ b ][1, 4]selenazines using a substoichiometric amount of Cu(OTf)2, through a base‐mediated 1, 4‐elimination at selenium, and generation of a dienic o ‐iminoselenoquinone